2010
DOI: 10.4040/jkan.2010.40.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Life Transition of Mothers of Children with Autism

Abstract: Purpose:While there are a number of studies on children with disabilities, there have been few studies on mothers of children with autism. The purpose of this study was to explore the process of life transition of mothers who have children with autism. Methods: From June 2007 to May 2009, the researcher interviewed 15 mothers of children with autism living in Seoul City, Gyeonggi or Chonbuk Provinces, and then analyzed the data gathered using the constant comparative method of grounded theory. Results: "Living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…특히, 아동이 어린 경우, 부모는 장애 진단을 최근에 받았거나 치료를 시작하는 시점에 있으므로 정서적 혼란 상태에서 스트레스와 우울 정도가 더 심하다 [6]. 그러 나 시간이 흐름에 따라 아동이 성장하면서 부모들은 점차적으로 정서적으로 안정되고 삶에 대한 태도도 긍정적으로 변화되는 양상 을 보이기도 한다 [7,8]. Figure 1).…”
unclassified
“…특히, 아동이 어린 경우, 부모는 장애 진단을 최근에 받았거나 치료를 시작하는 시점에 있으므로 정서적 혼란 상태에서 스트레스와 우울 정도가 더 심하다 [6]. 그러 나 시간이 흐름에 따라 아동이 성장하면서 부모들은 점차적으로 정서적으로 안정되고 삶에 대한 태도도 긍정적으로 변화되는 양상 을 보이기도 한다 [7,8]. Figure 1).…”
unclassified
“…Parents of children with ASD are at higher risk of depression and more likely to need professional help [20][21][22][23][24][25]. Parents who have children with ASD experience LTP [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Meleis et al [10] further suggested that health and illness challenges involve a process of transition that also increases parents' vulnerability to poor health. In this regard, a series of studies by Lee et al [11][12][13][14] investigated how mothers of children with autism experienced life transitions, and suggested differentiated support and care at each stage. Mothers who have children with ASD experienced five phases of the Life Transition Process (LTP): denying, wandering, devoting, mind controlling, and accepting [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations